To solve this system of equations, we will substitute the expression for x from the second equation into the first equation:
2(5y-1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
16y = -16
y = -1
Now that we have found the value of y, we can substitute it back into the second equation to find x:
x = 5(-1) - 1
x = -5 - 1
x = -6
Therefore, the solution to the system of equations is x = -6, y = -1.
Solving equations using subtraction, quick check
Solve the system of equations . 2x + 6y = - 18; x = 5y - 1 (1 point)
1 answer